Kemurnian Dan Stabilitas Radiokimia 153SmCl3 dengan Ligan EDTMP (Ethylene Diamine Tetramethylene Phosphanate) yang Berasal dari Tulang Sapi - Fitria, Najmiatul; Djamal, Rusdi; Muthalib, Abdul (Universitas Andalas, 2012)
Purity and stability evaluation post-production of labelled compound 153SmCl3 with EDTMP have been studied. Purity evaluation of 153SmCl3 and 153Sm-EDTMP were conducted using thin layer chromatographic principle on Whatman No.1. Stability evaluation of 153SmCl3 and 153Sm-EDTMP were conducted using visual observation on color and pH changes. Table showes that purity of 153Sm-EDTMP was Â± 98- 99 %. It means Â± 1-2 % rest was free 153Sm+3 which is left on drop point chromatographic paper. Table also describes t-student analyses that t (-0.545) < t table (2.306). It means storage time did not affect the purity of 153Sm-EDTMP.